2017
DOI: 10.1016/j.virusres.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Sequential transmigration of polymorphonuclear cells and naive CD3 + T lymphocytes across the blood-cerebrospinal-fluid barrier in vitro following infection with Echovirus 30

Abstract: Viral meningitis by non-polio enteroviruses (NPEV) is a major public health burden causing fatal outcomes especially in the younger population. Strong evidence exists that the blood-cerebrospinal-fluid (CSF) barrier (BCSFB) serves as an entry point for enterovirus and leucocytes into the central nervous system (CNS). Moreover, analysis of clinical CSF specimens of patients with a NPEV infection revealed a predominance of polymorphonuclear granulocytes (PMN) in the early phase and mononuclear cells in the later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 123 publications
(147 reference statements)
2
15
0
Order By: Relevance
“…Preliminary observations made with the Th cell subsets used in the present study confirm involvement of GPCR signaling in the diapedesis of all Th subsets across BLEC monolayers. Furthermore, our previous studies have shown that addition of exogenous CXCL12 to the CSF side increased T-cell migration across HIBCPP monolayers [31,68,69]. These data support the additional role for GPCR signaling in the migration of effector Th cell subsets across the BBB and BCSFB.…”
Section: Discussionsupporting
confidence: 74%
“…Preliminary observations made with the Th cell subsets used in the present study confirm involvement of GPCR signaling in the diapedesis of all Th subsets across BLEC monolayers. Furthermore, our previous studies have shown that addition of exogenous CXCL12 to the CSF side increased T-cell migration across HIBCPP monolayers [31,68,69]. These data support the additional role for GPCR signaling in the migration of effector Th cell subsets across the BBB and BCSFB.…”
Section: Discussionsupporting
confidence: 74%
“…Infection with EV30 results in the upregulation of the chemokines CXCL-3, -10, -11, -20 as well as IL-8 and macrophage colony-stimulating factor (M-CSF). During EV30 infection, there is predominantly a polar direction of cytokine/chemokine secretion in the basolateral side of the CP, with only IL-7 being secreted on the apical side to the CSF [162].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…For assessment of PMN and T-cell transmigration across the HIBCPP cell layer, an infection experiment over 24 h with an MOI of 0.7 was carried out. As recently described, PMN and naïve CD3 + T-cells were isolated from human blood of healthy donors [ 23 ]. Each cell population was labelled either with CellTrace™ Calcein red-orange or with CellTrace™ Calcein green (Molecular probes, USA) according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of different NPEVs on the barrier function and morphology of the BCSFB has not been investigated yet. Previously, it could be demonstrated that E-30 Bastianni can infect human choroid plexus epithelial (HIBCPP) cells and lead to alteration of barrier function [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation